Does meaning protect against loneliness? Exploring empirical studies and theory. (24th August 2020) - Folker, Anna Paldam; Lauridsen, Sigurd Mørk; Hegelund, Emilie Rune; Wimmelmann, Cathrine Lawaetz; Flensborg-Madsen, Trine
Abstract: Research indicates that meaning in life is a protective factor for physical and mental health. Although loneliness is increasingly recognized as an important public health concern, no studies have investigated the potential of meaning in life to protect against loneliness. Based on an explorative interdisciplinary research strategy that comprises data from a cohort study, a strategic review of empirical literature and a conceptual analysis of the concept of meaning in life we explore the support for potential links between meaning in life and the protection against loneliness. We propose three different explanatory mechanisms; (i) that meaning in life promotes a positive orientation toward others, (ii) that meaning in life enhances interpersonal appeal and (iii) that meaning in life promotes a better ability to cope with loneliness. Theoretically, we explore the idea that the value of meaning in life ultimately concerns a social need to contribute to the realization of value that, at least in principle, can be shared and recognized by others. When people realize the value of meaning in life, they partake in a community of shared values, which links them to a social world in a way that may protect against the feeling of loneliness. Jointly the analyses point to the need for prospective studies on the role of meaning in life as a protective factor against loneliness and a potential novel focus for loneliness interventions.